The other side of the story – maternal perceptions of safety advice and information: a qualitative approach. (20th January 2015) - Ablewhite, J.; Kendrick, D.; Watson, M.; Shaw, I.
Abstract: Background: A qualitative study of maternal perceptions of home safety advice. The aim was to gain an understanding of maternal perceptions of and possible barriers to the implementation of home safety advice. Methods: Semi‐structured interviews with 37 mothers with a child aged less than 5 years of age; 16 were mothers living in an area of socio‐economic disadvantage (with a high rate of childhood unintentional injury), 21 were mothers living in an area of relative affluence (with a low rate of childhood unintentional injury). Thematic analysis was used to analyse the data. Results: Although some mothers living in both areas found talking to a health professional about child home safety was helpful, mothers in both areas tended to find talking to other mothers as being more helpful and they preferred this to talking to a professional. Barriers to obtaining safety advice from professionals exist for mothers living in both areas. Mothers living in the advantaged area describe 'feeling silly' and that they should 'know it already' when talking to professionals. Mothers living in the disadvantaged area are less likely to access home safety advice due to fear of being perceived as an incompetent mother and the fear of social service involvement. Conclusions: Mothers find home safety advice from other parents more useful and prefer this to advice from professionals. This suggests greater use could be made of appropriately trained parents to deliver safety advice and education. Fear and mistrust can limit access to child safety advice in parents living in disadvantaged areas and this may be a potential explanation for differential unintentional injury rates as those who need the advice and support most may be least likely to access it. Further research should explore how professionals can build trust, gain parents' confidence and provide child safety advice and education that is targeted appropriately to parents living circumstances and their child safety needs.